2015
DOI: 10.1097/maj.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Metastatic Infection in Patients With Bacteremia Caused by Methicillin-Sensitive Staphylococcus aureus

Abstract: Abstract:Background:Metastatic infections such as infective endocarditis and psoas abscess are serious complications of Staphylococcus aureus bacteremia because failure to identify these infections may result in bacteremia relapse or poor prognosis. In the present study, we determined the predictive factors for metastatic infection due to methicillin-sensitive S. aureus bacteremia.Methods:A retrospective cohort study was conducted among patients with methicillin-sensitive S. aureus bacteremia at the Jikei Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
7
28
0
2
Order By: Relevance
“…Previous Japanese observational studies reported an inconsistent rate of pneumonia. One observational study reported a similar rate of pneumonia (17/83, 21%)6 as that reported in the present study, but another study reported a lower rate of pneumonia (4/73, 5%) 7. In contrast, the studies of SAB that were undertaken outside of Japan generally reported a low rate of pneumonia 9, 10.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous Japanese observational studies reported an inconsistent rate of pneumonia. One observational study reported a similar rate of pneumonia (17/83, 21%)6 as that reported in the present study, but another study reported a lower rate of pneumonia (4/73, 5%) 7. In contrast, the studies of SAB that were undertaken outside of Japan generally reported a low rate of pneumonia 9, 10.…”
Section: Discussionsupporting
confidence: 75%
“…In Japan, there have been several small observational studies about SAB, involving fewer than 100 patients 4, 5, 6, 7. These were all single‐center, rather than multicenter studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bones, joints, the kidneys, and the lungs are common sites of metastatic infections (1), and SAB occasionally involves the eyes (2). Previous studies showed that the incidences of metastatic infections due to SAB range between 13% and 39% (3)(4)(5)(6)(7)(8)(9)(10). Searching for metastatic infections in SAB is crucial, because such infections determine the duration of antibiotic therapy required and often necessitate adjuvant therapy such as drainage or surgery (11).…”
mentioning
confidence: 99%
“…Several predictive factors associated with the development of metastatic infection were identified including a delay in appropriate antimicrobial treatment of .48 hours, persistent fever for .72 hours after starting antibiotic treatment, and low C-reactive protein levels of .3 mg/dL during 2 weeks after the onset of bacteremia. 23 S. aureus colonization via nasal carriage has received attention as a source of infection in patients undergoing HD. A study conducted in Taiwan evaluated the nasal carriage of MRSA and subsequent infection among dialysis patients, health care workers, and their families within a single dialysis unit.…”
mentioning
confidence: 99%